Almost Unbiased Ratio cum Product Estimator for Finite Population Mean with Known Median in Simple Random Sampling - Jambulingam, Subramani; Master, Ajith S. (Nepalese Journal of Statistics, 2017)
Introduction: In sampling theory, different procedures are used to obtain the efficient estimator of the population mean. The commonly used method is to obtain the estimator of the population mean is simple random sampling without replacement when there is no auxiliary variable is available. There are methods that use auxiliary information of the study characteristics. If the auxiliary variable is correlated with study variable, number of estimators are widely available in the literature. Objective: This study deals with a new ratio cum product estimator is developed for the estimation of population mean of the study variable with the known median of the auxiliary variable in simple random sampling. Materials and Methods: The bias and mean squared error of proposed estimator are derived and compared with that of the existing estimators by analytically and numerically. Results: The proposed estimator is less biased and mean squared error is less than that of the existing estimators and from the numerical study, under some known natural populations, the bias of proposed estimator is approximately zero and the mean squared error ranged from 6.83 to 66429.21 and percentage relative efficiencies ranged from 103.65 to 2858.75. Conclusion: The proposed estimator under optimum conditions is almost unbiased and performs better than all other existing estimators. Nepalese Journal of Statistics, 2017, Vol. 1, 1-14